2016
DOI: 10.1016/j.riit.2016.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Efecto de la sulfonación del estireno-éster acrílico sobre las propiedades de las membranas de intercambio protónico

Abstract: In this work was studied the effect of sulfonation of styrene-acrylic ester and of titanium dioxide nanoparticles on the proton exchange membranes. It was evaluated the physicochemical characterization of membranes, such as, the water uptake capacity, ion exchange capacity, the mechanic properties of stress/strain, and the chemical functional groups present in the membrane structure by FTIR analysis. Water uptake increases with increasing the time of sulfonation reaction, reaching 60.9% after 8 hours of sulfon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…To obtain water absorption capacity, dry membranes were weighed (Ws), then immersed in distilled water at room temperature for 24 hours, after this time they Synthesis of a proton exchange membrane 997 were removed from the water and weighed again (Wh). The percentage of water retained was calculated with the following equation [2].…”
Section: Characterization Of the Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain water absorption capacity, dry membranes were weighed (Ws), then immersed in distilled water at room temperature for 24 hours, after this time they Synthesis of a proton exchange membrane 997 were removed from the water and weighed again (Wh). The percentage of water retained was calculated with the following equation [2].…”
Section: Characterization Of the Membranesmentioning
confidence: 99%
“…Within this group are the proton exchange membranes fuel cells (PEMFC) which do not present generation of polluting gases, but which have had a slow introduction to the market and high electrolyte costs. Reason for which it is necessary to characterize new polymers or polymer mixtures [2,3] that allow to continue with the development of fuel cells. It has been shown that the addition of inorganic filler tends to improve the characteristics of the polymeric membrane such as water retention, ion exchange and mechanical properties [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…The ion exchange capacity was determined by introducing the membranes in a 1M HCl solution for 24 hours at room temperature, then submerged in a 1 M NaCl solution for 24 hours. After, the protons released from the membranes were titrated with a 0.01M NaOH solution [6]. The breaking strain, the elongation to rupture and the Young's modulus of each synthesized membrane were measured with an EZ-S Universal Shimadzu texturometer.…”
Section: Characterization Of the Membranesmentioning
confidence: 99%
“…The reference Nafion® are the most used membranes commercially due their high proton conductivity, and mechanical and chemical stability, but they have disadvantages such as heavy reliance on hydration, reduction of conductivity at temperatures above the ambient and high cost [5]. Studies show that the addition of inorganic filler tends to improve the physicochemical properties of the membrane [5,6]. In this work, proton exchange membranes are obtained from n-butyl acrylate/styrene copolymer, modified with load of ferric oxide to evaluate its application in fuel cells.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to study new polymeric materials that can be used in these devices. It has been reported that the application of sulfonation reaction tends to improve the physicochemical and mechanical characteristics of the polymer [3,4].…”
Section: Introductionmentioning
confidence: 99%